Toll like receptor signaling pathway as a potential therapeutic target in colorectal cancer. Issue 8 (1st March 2018) - Moradi‐Marjaneh, Reyhaneh; Hassanian, Seyed Mahdi; Fiuji, Hamid; Soleimanpour, Saman; Ferns, Gordon A.; Avan, Amir; Khazaei, Majid
Abstract : Toll like receptor (TLR) signaling is involved in activating innate and adaptive immune responses and plays a critical role in inflammation‐induced diseases such as colorectal cancer (CRC). Dysregulation of this signaling pathway can result in disturbance of epithelial layer hemostasis, chronic inflammatory, excessive repair responses, and development of CRC. There is now substantial evidence for the benefit of targeting of this pathway in cancer treatment, and several agents have been approved, such as BCG (Bacillus Calmette Guérin), MPL (monophosphoryl lipid A) and imiquimod. This review summarizes the current knowledge about the different functions of TLRs on tumor cells and their application in cancer therapy with particular emphasis on recent preclinical and clinical research in treatment of CRC.